ESR2 Drives Mesenchymal-to-Epithelial Transition in Triple-Negative Breast Cancer and Tumorigenesis In Vivo - Piperigkou, Zoi; Koutsandreas, Anastasios; Franchi, Marco; Zolota, Vasiliki; Kletsas, Dimitrios; Passi, Alberto; Karamanos, Nikos K. (Frontiers in Oncology, 2022)
Estrogen receptors (ERs) have pivotal roles in the development and progression of triple-negative breast cancer (TNBC). Interactions among cancer cells and tumor microenvironment are orchestrated by the extracellular matrix that is rapidly emerging as prominent contributor of fundamental processes of breast cancer progression. Early studies have correlated ERβ expression in tumor sites with a more aggressive clinical outcome, however ERβ exact role in the progression of TNBC remains to be elucidated. Herein, we introduce the functional role of ERβ suppression following isolation of monoclonal cell populations of MDA-MB-231 breast cancer cells transfected with shRNA against human ESR2 that permanently resulted in 90% reduction of ERβ mRNA and protein levels. Further, we demonstrate that clone selection results in strongly reduced levels of the aggressive functional properties of MDA-MB-231 cells, by transforming their morphological characteristics, eliminating the mesenchymal-like traits of triple-negative breast cancer cells. Monoclonal populations of shERβ MDA-MB-231 cells undergo universal matrix reorganization and pass on a mesenchymal-to-epithelial transition state. These striking changes are encompassed by the total prevention of tumorigenesis in vivo following ERβ maximum suppression and isolation of monoclonal cell populations in TNBC cells. We propose that these novel findings highlight the promising role of ERβ targeting in future pharmaceutical approaches for managing the metastatic dynamics of TNBC breast cancer.